Penggunaan Media Gambar Dalam Meningkatkan Prestasibelajar Peserta Didik Kelas IV SDK ST. Andreas Paumere Pada Mata Pelajaran IPS Di Kecamatan Nangapanda - Anselmus Mema (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
The purpose of this study was to determine the use of image media in improving the learning achievement of fourth grade students in social studies subjects in classroom action research using a qualitative approach. This research was conducted by following the model developed by Kemmis and MC. Taggart which was carried out in cycle II, then the data collection was carried out using the techniques of (1) Observation, (2) Interview (Interview), (3) Documentation (Documentation). , (4) Test, (5) Photo or Camera. In accordance with the data collected through the above technique, then it is analyzed descriptively qualitatively in the form of opinions from observations and interviews and quantitative descriptive as supporting data in the form of numbers obtained from student learning outcomes through tests. The results of the research that was carried out in two cycles showed an increase in social studies learning achievement after the application of the Picture media.